Незвідна система обмежень для загального многогранника розміщень - Ємець, О.О.; Роскладка, О.В.; Недобачій, С.І. (Український математичний журнал, 2003)
Присвячено побудові системи обмежень для загального многогранника розміщені), що не містить надлишкових нерівностей. Одержання незвідної системи дозволяє сутгєво зменшити кількість операцій, необхідних для отримання точного розв'язку задач оптимізації на розміщеннях. We construct a system of restrictions for a general polyhedron of arrangements which does not contain surplus inequalities. The derivation of a nonreducible system enables one to significantly diminish a number of operations that arc necessary to obtain the exact solution of problems of the optimization on arrangements.